STRATEGI PEMBELAJARAN KETERAMPILAN BERBICARA DALAM BAHASA INGGRIS SEBAGAI BAHASA ASING PADA MAHASISWA INDONESIA - Sri Wahyuni; Elke Stracke (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
Abstract. This study investigates language learning strategies for speaking skills used by Indonesian EFL tertiary students. Such strategies have an effect on language learning outcomes and they can be learnt. This implies that less successful learners can make use of the present study findings to improve their strategy use, which may increase learning outcomes. In addition, among Indonesian EFL students, speaking is still highly intimidating, and hence more attention on this language skill is required. The study addresses how students use strategies, and why they use them in specific ways. This paper draws on interviews and learning diaries for speaking skills obtained from students (N = 20) at Gajayana University of Malang in Indonesia. The study demonstrates that the students used strategies consciously, confidently, effortfully, or persistently. The motives why they used the strategies in such specific ways are the perceived usefulness or pleasure in using the strategies. Thus, this research supports previous findings regarding conscious and confident use of strategies, but, additionally, uncovers effortful and persistent use of strategies as important approaches on how students use strategies. The study also confirms usefulness as an important motive why students use strategies, and emphasizes, at the same time, the students’ pleasure in using strategies. The paper concludes by discussing implications for theory and practice. Keywords: language learning strategies, speaking skills, ways of using language learning strategies, motives of using language learning strategies